Venomics proteomics - Othman, Iekhsan; Ahmad Rusmili, Muhamad Rusdi; Chowdhury, Mohd Ezharul; Ting, Tee Yee; Hodgson, Wayne C. (2013)
Malaysia is home for numerous venomous animals which are either terrestrial or marine. However, many of these venoms are not well studied and the active components of the toxins and venoms are remain biochemically and pharmacologically unknown. In recent years, advancement of proteomics technology has enabled rapid and massive discoveries in the composition of the venom of numerous animals. The technology could also help in understanding the venom and antivenom interaction and reactivity which could help the development of better antivenoms production. Novel bioactive discoveries made from utilization of proteomics technology not only enable the discoveries of various types of new novel toxin classes and isoforms of previously described toxins but also potentially new ones. In our laboratory, we are concentrating on the purification and characterization of new bioactive proteins and their isoforms for potential application not only in biomedical research but also in potential pharmaceutical and agricultural applications. There are five species of snakes of interest that currently being studied in our laboratory namely Bungarus candidus, Bungarus fasciatus, Naja naja kouthia, Ophiophagus hannah and Callosellasma rhodostoma. In order to selectively purify bioactive proteins of interest, we are using mass-spectrometry guided purification strategy to selectively purify bioactive proteins of interest. The purified bioactive proteins were then being characterized by using pharmacological and biochemical techniques to determine the activities such as neurotoxicity, cardiotoxicity, cytotoxicity and antibacterial properties. The bioactive proteins were analysed by using Q-TOF LCMS/MS for identification and de novo sequencing. By using this approach, we were successful in isolating several novel toxins which are currently undergoing characterizations. In conclusion, application of proteomics and mass spectrometry technologies provide a very rapid approach to purify known and identify unknown bioactive proteins from venoms. Application of these technologies could also help in understanding the composition and of venom and antivenom reactivity.